Peranan Lembar Kerja Mahasiswa berbasis eksperimen pada Mata Kuliah Konsep Dasar IPA - Muhammad Amran; Adnan K.; St. Asmah (Seminar Nasional LP2M UNM, 2019)
Experimental-based student worksheets in the basic science 2 subjects in the Basic Science Course 2 PGSD FIP UNM aims to make the lecture process run better and there are lecturer and student interactions. The results of observations from the lecturer indicate that when carrying out practical activities students really need student worksheets in the lecture process. The use of student worksheets in the lecture process will increase learning motivation when conducting lab work in the laboratory.